2016
DOI: 10.11604/pamj.2016.25.253.10018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of cryptosporidium in children aged 0- 5 years with diarrhea in Jos, Nigeria

Abstract: IntroductionCryptosporidium is an important cause of diarrhea in children and immune-compromised individuals. Recent advances in molecular diagnostics have led to the discovery of subtype families that are thought to be more commonly associated with diarrhea. We aimed to isolate and characterize Cryptosporidium spp among children with diarrhea in Jos, Nigeria.MethodsStool samples were collected from165 children aged 0-5 years with diarrhea. Cryptosporidium oocysts were examined by wet mount preparation, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…The 6.5% prevalence of Cryptosporidium infection in our study was within the range reported by other studies from Nigeria in children aged below 5 years. For example, a 4.8% prevalence among 165 children below 5-years of age with diarrhoea was found in Jos, with C. hominis the predominant species, as we found, and subtype Id [21]; a 5.6% prevalence of Cryptosporidium was reported in children with diarrhoea below 6-years of age from Ebonyi state, with both C. hominis and C. parvum identified and, among the C. hominis isolates, four different GP60 subtypes, including two in the Ia family [22]; a prevalence of Cryptosporidium infection was found in 11.1% of 21 diarrhoeic children less than 12 months of age from Oyo state; two of the isolates were C. hominis , both subtype IaA24R3 [23].…”
Section: Discussionmentioning
confidence: 72%
“…The 6.5% prevalence of Cryptosporidium infection in our study was within the range reported by other studies from Nigeria in children aged below 5 years. For example, a 4.8% prevalence among 165 children below 5-years of age with diarrhoea was found in Jos, with C. hominis the predominant species, as we found, and subtype Id [21]; a 5.6% prevalence of Cryptosporidium was reported in children with diarrhoea below 6-years of age from Ebonyi state, with both C. hominis and C. parvum identified and, among the C. hominis isolates, four different GP60 subtypes, including two in the Ia family [22]; a prevalence of Cryptosporidium infection was found in 11.1% of 21 diarrhoeic children less than 12 months of age from Oyo state; two of the isolates were C. hominis , both subtype IaA24R3 [23].…”
Section: Discussionmentioning
confidence: 72%
“…was found positive in 4.1% samples. A study was shown, where the prevalence of Cryptosporidium was 4.8% among children below five years of age with diarrhea [107]. A longitudinal cohort study was done on Bangladeshi slum children where the same procedure found Cryptosporidium positive cases in 6.3% cases [40].…”
Section: Discussionmentioning
confidence: 99%
“…There are few available studies on the prevalence of childhood (aged 0-5 years) Cryptosporidium infection in children. Three of these studies investigated the infection in both diarrhoeic and non-diarrhoeic children [33][34][35] , while the others studied the infection in only diarrhoeic children 36,19,37 and in malnourished children. 38 Methods employed by these studies include Modified Ziehl-Neelsen staining method; enzyme-linked immunosorbent assay technique (ELISA) and molecular methods (Table 2).…”
Section: Childhood Cryptosporidium In Nigeriamentioning
confidence: 99%
“…38 Methods employed by these studies include Modified Ziehl-Neelsen staining method; enzyme-linked immunosorbent assay technique (ELISA) and molecular methods (Table 2). Few available information on childhood cryptosporidiosis were reported for two states (Oyo and Osun) in south-western Nigeria, 33,35 two state (Jos and Zaria) in Northern Nigeria 19,34,37 and only one state in South Eastern Nigeria. 36 The overview of these reports according to tribes is represented in Fig.…”
Section: Childhood Cryptosporidium In Nigeriamentioning
confidence: 99%